Acute Alcohol Intoxication and Suicide Among United States Ethnic/Racial Groups: Findings from the National Violent Death Reporting System. (5th February 2013) - Caetano, Raul; Kaplan, Mark S.; Huguet, Nathalie; McFarland, Bentson H.; Conner, Kenneth; Giesbrecht, Norman; Nolte, Kurt B.
<x xml:space="preserve">Abstract</x> Background To assess the prevalence and sociodemographic correlates of suicide involving acute alcohol intoxication among U.S. ethnic minorities. Methods Data were derived from the restricted 2003 to 2009 National Violent Death Reporting System. The study focused on the sociodemographic and toxicological information of 59, 384 male and female suicide decedents for 16 states of the United States. Acute alcohol intoxication was defined as having a blood alcohol content (BAC) ≥0.08 g/dl. Overall, 76% of decedents were tested for the presence of alcohol. Results The proportion of suicide decedents with a positive BAC ranged from 47% among American Indians/Alaska Natives (AIs/ANs) to 23% among Asians/Pacific Islanders (PIs). Average BAC was highest among AIs/ANs. Among those who were tested for BAC, the proportion of decedents legally intoxicated prior to suicide was as follows: Blacks, 15%; AIs/ANs, 36%; Asians/PIs, 13%; and Hispanics, 28%. Bivariate associations showed that most suicide decedents who were legally intoxicated were male, younger than 30 years of age, with a high school education, not married, nonveterans, lived in metropolitan areas, and used a firearm to complete suicide. However, with the exception of Whites, most of these associations became not statistically significant in multivariate analysis. Conclusions Alcohol use and legal intoxication prior to completing suicide are common among U.S. ethnic groups, especially among men and those who are younger than 30 years of age. The AI/AN group had the highest mean BAC, the highest rate of legal intoxication and decedents who were particularly young. Suicide prevention strategies should address alcohol use as a risk factor. Alcohol problems prevention strategies should focus on suicide as a consequence of alcohol use, especially among AI/AN youth and young adults.